2001
DOI: 10.1038/sj.leu.2402302
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent administration of high-dose chemotherapy and rituximab is a feasible and effective chemo/immunotherapy for patients with high-risk non-Hodgkin's lymphoma

Abstract: The aim of this study was to investigate feasibility, tolerability and efficacy of rituximab-supplemented high-dose sequential chemotherapy (R-HDS) with peripheral blood progenitor cell autografting as frontline or salvage treatment in patients with advanced non-Hodgkin's lymphoma (NHL). Thirty-two patients have been treated: 14 at disease onset and 18 with relapsed or progressive disease. R-HDS regimens included six courses of rituximab. Rituximab was delivered either concurrently with high-dose chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…7,8 Furthermore, although rituximab efficacy has chiefly been proved in combination with conventional chemotherapy, it may also improve autograftbased programs, particularly as an in vivo purging agent before peripheral blood progenitor cell (PBPC) harvests. [9][10][11][12][13] Thus, rituximab-supplemented intensive programs with autograft might represent an effective alternative to R-CHOP in DLB-CL patients with unfavorable clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Furthermore, although rituximab efficacy has chiefly been proved in combination with conventional chemotherapy, it may also improve autograftbased programs, particularly as an in vivo purging agent before peripheral blood progenitor cell (PBPC) harvests. [9][10][11][12][13] Thus, rituximab-supplemented intensive programs with autograft might represent an effective alternative to R-CHOP in DLB-CL patients with unfavorable clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations have shown that HDS can easily be combined with Rituximab with the additive effect of powerful Rituximab-mediated in vivo purging. 55,56 Thus, Rituximab-supplemented HDS appears to be an attractive option in studies aiming to verify whether doseintensification is still worthwhile in the monoclonal antibody era. Randomized trials are ongoing and will hopefully provide an answer to this important matter (Ladetto et al, Blood 2005; 106 abstract 675).…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, the combination of Rituximab with repeated chemotherapy administrations had an in vivo purging effect, as demonstrated by the high frequency of PCR-negative harvests following hd-Ara-C observed in mantle-cell and relapsed follicular lymphoma patients. 44,45 Reduction of tumor contamination might explain the preferential use of PBPC collected after repeated chemotherapy courses.…”
Section: Discussionmentioning
confidence: 99%